Does corporate international diversification destroy value? Evidence from cross-border mergers and acquisitions - Dos Santos, Marcelo B.; Errunza, Vihang R.; Miller, Darius P. (Journal of Banking & Finance, 2008)
This paper investigates the valuation effects of corporate international diversification by examining cross-border mergers and acquisitions of US acquirers over the period 1990–2000. We find that, on average, acquisitions of “fairly valued” foreign business units do not lead to value discounts. In contrast, unrelated cross-border acquisitions result in a significant diversification discount of about 24% after accounting for the valuation of foreign targets. Furthermore, significant wealth gains accrue to foreign target shareholders regardless of the type of acquisition. Overall, our results suggest that international diversification does not destroy value while industrial diversification leads to discounts even after controlling for the pre-acquisition value of the target.